The Equity Dimension of Climate Change: Perspectives From the Global North and South - Seasons, Mark (2021)
The articles in this thematic issue represent a variety of perspectives on the challenges for equity that are attributable to climate change. Contributions explore an emerging and important issue for communities in the Global North and Global South: the implications for urban social equity associated with the impacts caused by climate change. While much is known about the technical, policy, and financial tools and strategies that can be applied to mitigate or adapt to climate change in communities, we are only now thinking about who is affected by climate change, and how. Is it too little, too late? Or better now than never? The articles in this thematic issue demonstrate that the local impacts of climate change are experienced differently by socio-economic groups in communities. This is especially the case for the disadvantaged and marginalized—i.e., the poor, the very young, the aged, the disabled, and women. Ideally, climate action planning interventions should enhance quality of life, health and well-being, and sustainability, rather than exacerbate existing problems experienced by the disadvantaged. This is the challenge for planners and anyone working to adapt to climate change in our communities.